Literature Review: Konflik dan Manajemen Konflik Di Rumah Sakit - Mardiyanthi, Indah; Sjattar, Elly Lilianty; Irwan, Andi Masyitha (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
ABSTRACTIntroduction: Conflict is a complex process that cannot be avoided. Demands that health workers can provide comprehensive services influence on increasing interaction between health workers. The purpose of this literature review is to obtain information about conflicts and their management in hospitals.Methods: Article searches were carried out in four database journals namely Google Scholar, ProQuest, Pubmed, and Wiley. The keywords used are